Intravoxel incoherent motion (IVIM) MR imaging of colorectal liver metastases: Are we only looking at tumor necrosis?. Issue 2 (30th May 2013) - Chiaradia, Melanie; Baranes, Laurence; Van Nhieu, Jeanne Tran; Vignaud, Alexandre; Laurent, Alexis; Decaens, Thomas; Charles‐Nelson, Anaïs; Brugières, Pierre; Katsahian, Sandrine; Djabbari, Marjane; Deux, Jean‐François; Sobhani, Iradj; et al.
Abstract : Purpose: To determine if intra‐voxel incoherent motion diffusion‐weighted imaging (IVIM‐DWI) parameters, including free molecular‐based (D) and perfusion‐related (D*, f) diffusion parameters, correlate with the degree of tumor necrosis and viable tumor in colo‐rectal cancer (CRC) metastasis. Materials and Methods: Fifteen patients referred for resection of liver metastases from CRC were retrospectively included in this Institutional Review Board approved study. An IVIM‐DWI sequence was performed on a 1.5 Tesla MR imaging system, with 10 b factors (0, 10, 20, 30, 50, 80, 100, 200, 400 and 800 s/mm 2 ). Mean D, D*, f and apparent diffusion coefficient (ADC) values were determined in metastases with a longest diameter above 10 mm. Correlations between the diffusion parameters and the degree of liver tumor necrosis and viable tissue were determined (Spearman). Results: Correlation between diffusion parameters and histopathological findings was performed in 35 hepatic metastases with a diameter of more than 10 mm (mean size of 17.9 mm; range, 1–68 mm). Both D (r = 0.36; P  = 0.035) and ADC (r = 0.4; P  = 0.02) correlated with the degree of tumor necrosis but not with viable tumor. Conclusion: ADC variation observed in CRC metastases following systemic chemotherapy reflects a specific increase in free‐molecular diffusion (D), in itself correlated to the degree of metastasis necrosis.J. Magn. Reson. Imaging 2014;39:317–325 . ©2013 Wiley Periodicals, Inc .